MicroRNA-490-3p inhibits colorectal cancer metastasis by targeting TGFβR1 - Xu, Xuehu (BMC Cancer, 2015)
BACKGROUND: Colorectal cancer (CRC) is one of the most common malignances worldwide. Metastasis is responsible for the rapid recurrence and poor prognosis of CRC. However, the underlying molecular mechanism of CRC metastasis remains largely unclear. In this study we purposed to investigate the expression and biological functions of miR-490-3p in CRC metastasis, as well as to identify its downstream target genes and influenced pathway. METHODS: The expression level of miR-490-3p in CRC cell lines, CRC adjacent normal tissues, non-metastasis and metastasis tissues were assessed by quantitative real-time PCR. Patient survivals were follow-up up to 7 years. Gain-of-function and loss-of-function study on cell migration and invasion abilities were carried out by transfection of miR-490-3p mimics or inhibitors respectively. The molecular targets of miR-490-3p were computationally identified and experimentally verified by dual-luciferase reporter assay and western blot. Functional rescue was also conducted to confirm miR-490-3p inhibits CRC metastasis by targeting TGF-β signaling pathway. RESULTS: miR-490-3p expression was persistently downregulated during CRC malignant progression, as well as in CRC cell lines. Artificially overexpression miR-490-3p in CRC cell lines inhibited cell migration and invasion abilities while knockdown miR-490-3p expression caused the reverse effects. TGFβR1 and MMP2/9 were the downstream targets of miR-490-3p in CRC. Inhibition of TGFβR1 could partially recover the tumor suppression effect of miR-490-3p. CONCLUSION: miR-490-3p is downregulated during CRC malignant progression. miR-490-3p represses CRC cell migration and invasion abilities, partially by targeting to the TGF-β signaling pathway. Taken together, miR-490-3p is acting as a tumor suppressor in CRC.